GAMBARAN PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG PERNIKAHAN DINI DI DESA KARANGLO KECAMATAN KEREK - Nurul Haromaini; Wahyu Tri Ningsih; Wahyuningsih Triana Nugraheni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Child marriage or early marriage is considered unsafe and harmful practice because of insufficient readiness in various aspects. In 2008, the prevalence of child marriage was 14,67% and decreased by 11,21% in 2018. The objective of this study was to determine the knowledge and attitudes of female adolescents about early marriage at Karanglo Village, Kerek Sub-District. This study was descriptive research with a cross-sectional approach. The population of this study was 155 people. The samples were 115 female adolescents. The sampling technique used simple random sampling. Research variables are the knowledge and attitudes of female adolescents about early marriage. The data collection technique used questionnaires and the data were analyzed descriptively in the form of a frequency table.The results found that almost all female adolescents have good knowledge (81%). Most female adolescents have a positive attitude (55%). Most female adolescents have good knowledge with positive attitudes (52,3%). Almost half of the female adolescents have good knowledge with negative attitudes (28,8%).Female adolescents at Karanglo village have good knowledge about early marriage. However, some of them who have good knowledge only know the basic knowledge of early marriage and many still have negative attitudes. Therefore, it is necessary to increase education and counseling about early marriage, starting from understanding the factors that influence the incidence of early marriage to the impact it has. Active participation of the Adolescent Integrated Health Service (Posyandu Remaja) in the Adolescent Reproductive Health (KRR) Education Program is one of the efforts to prevent early marriage. The role of parents and families can be a priority in providing education to children regarding adolescent reproductive health.Keywords: Knowledge, Attitudes, Early Marriage